Structural dependence of CsI(Tl) film scintillation properties - Ananenko, A.; Fedorov, A.; Lebedinsky, A.; Mateychenko, P.; Tarasov, V.; Vidaj, Yu. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2004)
Scintillating CsI(Tl) films were obtained by vacuum deposition on single crystalline LiF substrates and non-orienting glass substrates. Their structure and morphology were examined by X-ray diffraction and scanning electron microscopy. Scintillation properties of films dependent on their structure are discussed.